Problems of Law Enforcement in Realizing The Principle of Equality Before The Law in Indonesia - Rofingi, Rofingi; Rozah, Umi; Asga, Adifyan Rahmat (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2022)
Indonesia is a state of law. The law stipulates the principle of equality before the law. There are various problems in law enforcement. These problems have led to the failure to observe the principle of equality before the law. Just as the persecution suffered by Sarpan, the police admitted that they were the perpetrators of the murder. This is different from the case of Napoleón Bonarparte and Prasetijo Utomo, the suspect of bribery to remove red notice warrant of Djoko Tjandra. In this case, Djoko Tjandra had lunch with the head of the prosecutor's office. This research is significant considering the widespread practice of law enforcement that underestimates the principle of equality before the law, so it will not discriminate against everyone when applying the law in the future. This study uses the non-doctrinal reaserch because it examines laws and regulations and their implementation to the people. From this research, it is found that due to the problems of laws and regulations that are unsuitable for the people, lacked of ethics, beliefs, resources, and transparency in the screening of order agents, the principle of equality before the law has not been implemented, and there is inconsistency in the application of the law Integration leading to the decline in public trust to the law . Therefore, these issues need to be improved to realize the principle of equality before the law in law enforcement.